2007
DOI: 10.1016/j.actbio.2006.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Development of a device to stretch tissue-like materials and to measure their mechanical properties by scanning probe microscopy

Abstract: We developed a new stretch device to investigate the biomechanical responses to an external loading force on a tissue-like material consisting of cells and a collagen gel. Collagen gel, a typical matrix found abundantly in the connective tissue, was attached to an elastic chamber that was precoated with a thin layer of collagen. Madin-Darby canine kidney (MDCK) cells that were cultured on the collagen gel were stretched in a uniaxial direction via deformation of the elastic chamber. Changes in the morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A common approach is using gel construct for cyclic stretching (Vanderploeg et al 2008) where cells were seeded into liquid fibrin hydrogel conditioned with culture solution. Mechanical pulling using stepper motors or controllable linear stages was the common actuation technique (Lindqvist et al 2010, Pfister et al 2004, Mizutani et al 2007, Nguyen et al 2012. Stretching can be achieved wirelessly using magnetically actuated microposts (Sniadecki et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A common approach is using gel construct for cyclic stretching (Vanderploeg et al 2008) where cells were seeded into liquid fibrin hydrogel conditioned with culture solution. Mechanical pulling using stepper motors or controllable linear stages was the common actuation technique (Lindqvist et al 2010, Pfister et al 2004, Mizutani et al 2007, Nguyen et al 2012. Stretching can be achieved wirelessly using magnetically actuated microposts (Sniadecki et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We suggest two possible reasons for these results. First, the human iPS cell-derived telencephalic neuron aggregates are fragile and are thus suitable for culture on collagen gel, which is softer than the collagen or PDL/laminin/fibronectin coating (Yunoki et al, 2011, Mizutani et al, 2007. Alternatively, the cellular crawling into the 3D-pore structure in the collagen gel contributed to the tight adhesiveness between these aggregates and the collagen gel.…”
Section: Discussionmentioning
confidence: 99%
“…Our group modified a commercial AFM to wide-range scanning probe microscopy (WR-SPM) which enabled acquisition of elasticity and topography distribution of thick sample like epithelial tissue over sub-millimeter scan range [5]. By using the AFM or WR-SPM, some research groups showed that cell-cell boundaries are stiffer than the center of the cells [4,6]. In the present study, we measured a time course of topography and elasticity distribution of epithelial cells during regenerating cell-cell adhesion using WR-SPM.…”
Section: Introductionmentioning
confidence: 99%